The Effect of Literacy Interest and Student Participation Level in Learning on Student Learning Outcomes in Economics Subject for Class X at SMAN 1 Nan Sabaris, Padang Pariaman Regency - Roza, Silvia; Juwita, Sri Kurnia (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by the low learning outcomes of class X students of SMAN 1 Nan Sabaris, Padang Pariaman Regency. This is caused by low literacy interest and low student participation in the learning process. This study aims to determine the extent of influence of literacy interest and student participation in learning on student learning outcomes in economics for class X at SMAN 1 Nan Sabaris, Padang Pariaman Regency. This research is a correlational study. The population of this study was all 287 students of class X of SMAN 1 Nan Sabaris, Padang Pariaman Regency. The sampling technique used stratified proportional random sampling, totaling 167 students. The research instrument was a questionnaire measured using a Likert scale. The data analysis techniques used were prerequisite analysis and hypothesis testing. The results of this study indicate a positive and significant influence of literacy interest (X1) and student participation level in learning (X2) on economics learning outcomes (Y), with a significance value of 0.000 <0.05 and a calculated t-value of 7.377 >1.667 (t-table). Literacy interest and student participation level in learning have a coefficient (b1) of 0.038. This means that every 1% change in literacy interest will increase literacy interest by 3.8%. Furthermore, the coefficient (b2) is 0.058. This means that every 1% change in student participation level in learning will increase student participation level by 5.8%. The results of multiple regression testing indicate that the coefficient of determination (R2) of 30.3% of learning outcomes is influenced by literacy interest and student participation level in learning, while the remaining 69.7% is influenced by other variables not examined in this study.